PENGARUH MEDIA TEKA TEKI SILANG TERHADAP KEMAMPUAN BERPIKIR KRITIS DALAM PEMBELAJARAN BAHASA INDONESIA SISWA KELAS V SD - Fitriani , Silvy; Hetilaniar; Adrianus Dedy (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims to determine the effect of using crossword puzzle media on the critical thinking skills of fifth-grade students at SD Negeri 2 Mulyaguna in Indonesian language learning. The background of this research is based on the low critical thinking ability of students, as seen from their difficulty in understanding and analyzing expository texts. This study employed a quantitative method with a quasi-experimental design, specifically the Nonequivalent Control Group Design. The research subjects consisted of two classes: an experimental class using crossword puzzle media and a control class using conventional methods. Data were collected through essay tests based on critical thinking indicators. The data analysis results showed a significant difference between the post-test scores of the experimental and control classes. The experimental class achieved an average score of 81.6, while the control class scored an average of 52.6. Thus, the average score of the experimental class was higher than that of the control class. The use of crossword puzzle media has proven to positively influence the improvement of students' critical thinking skills. Therefore, crossword puzzles can serve as an innovative alternative to enhance the quality of Indonesian language learning in elementary schools.